Impact of COVID-19 on River and Fisheries: A Comprehensive Guide - , Durgesh Kumar Verma; , Shravan Kumar Sharma; , Ridhdhisa R. Barad; , Rajesh Jayaswal; , Pragati Inwati; , Ishwar Chandra; , Vivek Kumar; , Akanksha Kurmi; , Binal Rajeshbhai Khalasi (Archives of Current Research International, 2024)
Impact of COVID-19 on Rivers and Fisheries: A Comprehensive Guide is a review article that discusses the effects of the COVID-19 pandemic on the aquaculture sector (including financial assistance, input sub/sides, social protection, support for access to new markets, and other measures) aquatic environments, including rivers and fisheries. The authors highlight a significant reduction in tourism, which has led to a decline in the Indian economy. They also discussed the impact of the pandemic on the aquaculture industry, which has been severely affected by the reduction in demand. This review article further discusses the changes in water quality parameters, including increased plastic waste, improved water quality index due to reduced human activities and reduced availability of nutrients due to decreased agricultural activities. The authors also discussed the impact of the pandemic on fish biodiversity, including population restoration due to reduced industrial pollution and changes in the reproductive state of fish. The article concludes by discussing the impact of the pandemic on the exploitation of fish and the aquaculture and fishing industries, including increased fishing effort and harvest with prolonged lockdowns and decreased fish production.